How does market react to corporate spin-offs in Australia? - Nguyen, Xuan Truong (University of Economics Ho Chi Minh City, 2023)
While numerous studies on spin-off have been done in the US and Europe, little efforts have been directed to research this area of cor-porate finance in Australia. This study investigates how market re-acts to corporate spin-offs in this country. We employ traditional event study methodology and find that market reacts strongly and positively to the announcements of spin-offs. Specifically, the cu-mulative average abnormal return over the 3-day event window is 3.58%. The cumulative average abnormal return for spin-offs by companies that increase their industrial focus is 4.12% and 3.33% for non-focused increasing spin-offs. Nevertheless, the difference between these two subgroups is statistically insignificant. Multivari-ate regressions provide evidence that high pre-leverage firms benefit more from spin-offs.